Colicins exploit native disorder to gain cell entry: a hitchhiker's guide to translocation. (19th November 2008) - Bonsor, Daniel A.; Meenan, Nicola A.; Kleanthous, Colin
Abstract : The translocation of protein toxins into a cell relies on a myriad of protein–protein interactions. One such group of toxins are enzymatic E colicins, protein antibiotics produced by Escherichia coli in times of stress. These proteins subvert ordinary nutrient uptake mechanisms to enter the cell and unleash nuclease activity. We, and others, have previously shown that uptake of ColE9 (colicin E9) is dependent on engagement of the OM (outer membrane) receptors BtuB and OmpF as well as recruitment of the periplasmic protein TolB, forming a large supramolecular complex. Intriguingly, colicins bind TolB using a natively disordered region to mimic the interaction of TolB with Pal (peptidoglycan-associated lipoprotein). This is thought to trigger OM instability and prime the system for translocation. Here, we review key interactions in the assembly of this 'colicin translocon' and discuss the key role disorder plays in achieving uptake.